2013
DOI: 10.5665/sleep.2628
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis-in-Drop Array for MonitoringC. elegansQuiescent Behavior

Abstract: CiD is useful for the analysis of behavioral quiescence during lethargus as well as during the adult stage C. elegans. The method is expandable to parallel simultaneous monitoring of hundreds of animals and for other studies of long-term behavior. Using this method, we were successful in measuring, for the first time, quiescence in kin-2(ce179) and in acy-2(ce2) mutants, which are hyperactive. Our observations also highlight the impact of environmental conditions on quiescent behavior and show that longevity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 46 publications
(44 reference statements)
4
41
0
Order By: Relevance
“…The signaling pathways investigated here, as well as other previously identified regulators of DTQ Singh et al, 2011;Belfer et al, 2013;Choi et al, 2013;Driver et al, 2013;Iwanir et al, 2013;Nagy et al, 2013;Nelson et al, 2013;Schwarz and Bringmann, 2013;Turek et al, 2013;Nagy et al, 2014;Singh et al, 2014;Choi et al, 2015) and SIQ (Hill et al, 2014;, are found in many cell and neuron types and are highly conserved. These pathways have been implicated in sleep regulation in a variety of species (Allada and Siegel, 2008;Crocker and Sehgal, 2010), but their ubiquitous expression patterns have made identification of specific cellular and circuit functions for these pathways challenging (but see Crocker et al, 2010).…”
Section: Why Is Quiescence During Dtq and Siq Engaged Differently?mentioning
confidence: 61%
See 2 more Smart Citations
“…The signaling pathways investigated here, as well as other previously identified regulators of DTQ Singh et al, 2011;Belfer et al, 2013;Choi et al, 2013;Driver et al, 2013;Iwanir et al, 2013;Nagy et al, 2013;Nelson et al, 2013;Schwarz and Bringmann, 2013;Turek et al, 2013;Nagy et al, 2014;Singh et al, 2014;Choi et al, 2015) and SIQ (Hill et al, 2014;, are found in many cell and neuron types and are highly conserved. These pathways have been implicated in sleep regulation in a variety of species (Allada and Siegel, 2008;Crocker and Sehgal, 2010), but their ubiquitous expression patterns have made identification of specific cellular and circuit functions for these pathways challenging (but see Crocker et al, 2010).…”
Section: Why Is Quiescence During Dtq and Siq Engaged Differently?mentioning
confidence: 61%
“…We focused in particular on strains with increased neurotransmitter release due to increased G␣q and G␣s signaling (Fig. 2, adapted from Perez-Mansilla and Nurrish, 2009), since these mutants show hyperactive locomotion and some have defects in DTQ locomotion quiescence (Belfer et al, 2013;Iwanir et al, 2013;Schwarz and Bringmann, 2013;Singh et al, 2014), and therefore they might be resistant to the effects of somnogenic neuropeptides.…”
Section: Activation Of the G␣q Or G␣s Pathways Inhibits Both Flp-13-amentioning
confidence: 99%
See 1 more Smart Citation
“…Ostriches have been behaviorally and electrophysiologically evaluated in their natural habitat [114] as have rain-forest-dwelling sloths [115]. Technical improvements in tracking Drosophila activity utilizing green fluorescent protein with three-dimensional (3-D) video monitoring hold promise for more refined analyses of behavior, and a new technique utilizing an array of aqueous droplets, rather than an agar surface, for studies in the roundworm, C. elegans, suggests a more efficient technique for evaluation of manipulations [116,117].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the droplet is an isolated space, the motility of the worm can be simply correlated with the fluid drag and wall frictions. Our past results 16 and some papers [17][18][19][20] have reported that worms in such a confined and aqueous environment tend to be more active but short-lived perhaps due to reduced mechanical load in liquid, 20 a different motor program in liquid, 19 accumulation of metabolic waste, or food shortage. 16 Nevertheless, the aqueous system remains an ideal platform to date for analyzing the biomechanics of the nematodes 21 when the motility in liquid is interested and the measurement period is less a few hours.…”
Section: Introductionmentioning
confidence: 99%